Intrinsic plasmids influence MicF-mediated translational repression of ompF in Yersinia pestis - Liu, Zizhong; Wang, Haili; Wang, Hongduo; Wang, Jing; Bi, Yujing; Wang, Xiaoyi; Yang, Ruifu; Han, Yanping (Frontiers in Microbiology, 2015)
Yersinia pestis, which is the causative agent of plague, has acquired exceptional pathogenicity potential during its evolution from Y. pseudotuberculosis. Two laterally acquired plasmids, namely, pMT1 and pPCP1, are specific to Y. pestis and are critical for pathogenesis and flea transmission. Small regulatory RNAs (sRNAs) commonly function as regulators of gene expression in bacteria. MicF, is a paradigmatic sRNA that acts as a post-transcriptional repressor through imperfect base pairing with the 5’-UTR of its target mRNA, ompF, in Escherichia coli. The high sequence conservation and minor variation in the RNA duplex of MicF-ompF has been reported in Yersinia. In this study, we utilized super-folder GFP reporter gene fusion to validate the post-transcriptional MicF-mediated regulation of target mRNA ompF in Y. pestis. Unexpectedly, upon MicF overexpression, the slightly upregulated expression of OmpF were found in the wild-type strain, which contradicted the previously established model. Interestingly, the translational repression of ompF target fusions was restored in the intrinsic plasmids-cured Y. pestis strain, suggesting intrinsic plasmids influence the MicF-mediated translational repression of ompF in Y. pestis. Further examination showed that plasmid pPCP1 is likely the main contributor to the reversal of MicF-mediated translational repression of ompF. It represents that the possible roles of